Feasibility Analysis of Large Red Chili (Capsicum Annum L.) Farming in Tawangargo, Karangploso, Malang, Indonesia, Across Wet and Dry Seasons - Irma Miranda; Dyah Erni Widyastuti; M. Zul Mazwan (Universitas Muhammadiyah Malang, 2023)
This study investigates the financial feasibility of large red chili (Capsicum annum L.) farming during both the rainy and dry seasons in Tawangargo, Karangploso, Malang, Indonesia. Many farmers in this region do not thoroughly evaluate the costs and revenues associated with their farming practices, leading to uncertainty regarding the financial feasibility of large red chili farming. The primary aim of this research is to assess the financial feasibility of such farming practices across seasons and to compare their financial viability. The research employs the analysis of the Revenue-to-Cost (R/C) ratio and a paired sample t-test to evaluate the financial feasibility of large red chili farming. Our findings reveal that large red chili farming in both rainy and dry seasons is financially feasible. The R/C ratio for the rainy season is 2.12, and for the dry season, it is 1.51, both of which exceed the critical threshold of 1, indicating the financial feasibility of farming and developing large red chili in this region. The results of the Paired Sample Test demonstrate significant differences in the financial feasibility of large red chili farming between the rainy and dry seasons in Tawangargo, Karangploso, Malang, Indonesia. The average of income per-hectare for large red chili farming is IDR 101,573,764 during the rainy season and IDR 45,393,331 during the dry season.